The influence of the press of the party leadership of Kazakhstan in the ninth five-year plan on military personnel (1971-1975) - Karekenov, М.; Shurentayev, А.; Azhgaliyev , М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
In the article, articles and scientific papers related to the influence of the press of the party leadership of Kazakhstan on military personnel of the ninth five-year plan were considered in the most complete form. The experience of managing Press services carried out by party organizations of the Republic during the Communist Party period was studied in a comprehensive manner. In the course of the research, the study, generalization and scientific substantiation of works on this topic, ways to identify effective forms and methods of publishing management were considered. Ways to improve and implement them have been identified. It is noted that the leadership of the party and the Soviet government paid special attention to the development of the party-Soviet press system of Kazakhstan at that time and the training, education and further development of journalistic personnel. We are talking about how the party-Soviet publishing house of the Republic affected the personnel of military personnel. It is about his work to monitor how the propaganda and organizational role of the Central Committee of the CPSU in the spirit of the demands of the "Communist Party of Kazakhstan" was strengthened by the press service of each serviceman. The article focuses on ways to study and improve the effectiveness of various problems of the press and propaganda, in which military forces interact with the mass media. It shows the special influence of the Central Press on increasing the role of the Republican (local) press in solving the problems of communist construction by communicating them to the military environment through printed pages. We will talk about the practical work of a number of mass media aimed at improving the activities of party organizations for soldiers who serve their country faithfully in the ranks of the army. In this article, it is widely reported about the influence of the press of the party leadership of Kazakhstan on military personnel.